Can Radiographs Predict Outcome in Patients With Idiopathic Clubfeet Treated With the Ponseti Method?. Issue 7 (October 2015) - O'Halloran, Conor P.; Halanski, Matthew A.; Nemeth, Blaise A.; Zimmermann, Catherine C.; Noonan, Kenneth J.
Abstract : Background: The aim of this study was to determine if radiographic measurements, taken before tenotomy, can predict outcome in children with idiopathic clubfoot treated by the Ponseti method. Methods: A retrospective chart and radiographic review was performed on children with idiopathic clubfoot treated with the Ponseti method over a 10-year period with minimum 2-year follow-up that had a forced dorsiflexion lateral foot radiograph before tenotomy. All angles were measured in duplicate on the pretenotomy radiographs, including: foot dorsiflexion (defined as the 90 minus the angle between the tibial shaft and a plastic plate used to dorsiflex the foot), tibio-calcaneal, talo-calcaneal, and talo-first metatarsal angles. Clinical review of patient records identified different patient outcomes: no additional treatment required, relapse (additional casting and/or surgery required), recurrence (any additional surgery required), or reconstruction (surgery not including repeat tenotomy). Results: Forty-five patients (71 feet) were included in the study. The median age at follow-up was 4.6 years. The intrareader reliability was acceptable for all measures. Thirteen of the 71 (18%) feet required additional surgery, occurring at a median age of 3.6 years. Of the 4 radiographic measures, only pretenotomy foot dorsiflexion predicted recurrence (hazard ratio=0.96, P =0.03). Youden's method identified 16.6 degrees of dorsiflexion as the optimal cutoff. Feet with at least that amount of dorsiflexion pretenotomy (n=21) experienced no recurrences; feet with less than that amount of dorsiflexion (n=50) experienced 13 recurrences ( P =0.007). Conclusions: Reduced foot dorsiflexion on lateral forced dorsiflexion pretenotomy radiograph was associated with an increased risk of recurrence. Radiographic dorsiflexion to 15 degrees past neutral before tenotomy appears to predict successful treatment via the Ponseti method. Level of Evidence: Level IV.